Developing TalkBuddy : An Inclusive Android Application for Deaf Students' English Learning and Statistical Support - Friska, Yuliana; Husnul, Nisak Ruwah Ibnatur; Ibnurhus, Gigih Amrillah (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop the Android-based application Talkbuddy as an inclusive communication medium for teaching English and Statistics to deaf students at Universitas Pamulang. The application is designed to address communication challenges in learning by incorporating features such as speech-to-text transcription, group discussion forums, access to learning modules, educational videos, the latest news in education, and a space for sharing experiences. This research adopts the Research and Development (R&D) method using the Luther-Sutopo model, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The trial was conducted with two deaf students who participated in a series of application usage tests to evaluate the effectiveness and practicality of the developed features. Data collection techniques included interviews, observations, and questionnaires throughout the trial process. Data analysis was conducted through expert validation (content and media), alpha testing, and beta testing. The results indicate that the Talkbuddy application enhances communication accessibility and supports inclusive learning processes in English and Statistics courses, with average scores in alpha and beta testing exceeding 80, indicating a high level of feasibility. This application offers an innovative solution to the academic communication barriers faced by deaf students and is expected to contribute to the advancement of inclusive learning technology in higher education.